Optimization of electrochemical activation of persulfate by BDD electrodes for rapid removal of sulfamethazine. (January 2022) - Nashat, Mohamed; Mossad, Mohamed; El-Etriby, Hisham Kh; Gar Alalm, Mohamed
Abstract: Boron-doped diamond electrodes have been employed for the removal of sulfamethazine (SMZ) from water by electrochemical activation of persulfate (EO/BDD-PS). A set of experiments with a central composite design (CCD) was conducted to optimize the operating parameters such as persulfate dose, solution pH, and current density by response surface methodology (RSM). The experimental results indicated a rapid degradation of SMZ even at high initial concentrations. For instance, complete degradation of 50 mg L −1 of SMZ was attained after 15 min at the optimum operating conditions (persulfate loading = 0.40 g L −1, pH = 4, and current density = 21 mA cm −2 ). The oxidation mechanism of EO/BDD-PS process was studied based on the reactive oxidant species (ROS) revealing that both (OH) and contributed to the degradation of SMZ in the EO/BDD-PS system. Furthermore, the oxidation pathway has been proposed by the suspect screening and tandem mass spectrometry analysis. The performance of EO/BDD-PS showed faster SMZ degradation than electro-Fenton and anodic oxidation processes using the same BDD electrochemical reactor under the same conditions. Furthermore, we provided a cost estimation study revealing that a full-scale application of the EO/BDD-PS system for the treatment of similar contaminated water costs about 2.23 m -3 . Graphical abstract: Image 1 Highlights: Persulfate was electrochemically activated by BDD electrodes. Complete degradation of SMZ was rapidly achieved by the EO/BDD-PS system. The degradation of SMZ by EO/BDD-PS was optimized by RSM. The EO/BDD-PS system was notably faster than anodic oxidation and electro-Fenton. The cost of application of the EO/BDD-PS system was determined to be 2.23 m -3 .